Pendekatan Kontekstual Dalam Kegiatan Belajar Mengajar - Farida Catur Wahyu Angggriyani (STAI Sangatta Kutai Timur, 2020)
Abstract: Education is one of the important factors in human life, society and the nation in an effort to improve welfare, skills and skills towards a better direction. With education, it is hoped that it can give birth to people who are better able to build themselves, society and the nation. Various learning approaches have been widely discussed and implemented in teaching and learning activities, but the process and results have not been as expected by the goals of education and teaching. One of the learning approaches that are trying to be offered to eliminate this problem is the Contextual Teaching and Learning (CTL) approach. The CTL approach is a learning concept that helps teachers link the material being taught with students' real-world situations and encourages students to be able to contain the relationship between their knowledge and its application in their daily lives. In its application, the CTL approach has seven main components, namely (1) constructivism, (2) inquiry, (3) questioning, (4) learning community, (5) modeling, (6) reflection, and (7) the actual assessment (authentic assessment). Through the CTL approach, the knowledge and skills that students acquire are a construction of the student's experience. Abstrak Pendidikan merupakan salah satu faktor yang penting dalam kehidupan manusia, masyarakat dan bangsa dalam usaha meningkatkan kesejahteraan, kecakapan dan keterampilan menuju kearah yang lebih baik. Dengan pendidikan diharapkan dapat melahirkan manusia yang lebih mampu membangun dirinya sendiri, masyarakat dan bangsa. Berbagai pendekatan pembelajaran sudah banyak di diskusikan dan dilaksanakan dalam kegiatan belajar mengajar, tetapi proses dan hasilnya belum seperti yang diharapkan oleh tujuan pendidikan dan pengajaran. Salah satu pendekatan pembelajaran yang coba ditawarkan untuk mengeliminasi persoalan tersebut adalah pendekatan Contexttual Teaching and Learning (CTL). Pendekatan CTL adalah konsep pembelajaran yang membantu guru mengaitkan antara materi yang diajarkan dengan situasi dunia nyata siswa dan mendorong siswa agar dapat memuat hubungan antara pengetahuan yang dimiliki dengan penerapannya dalam kehidupan mereka sehari-hari. Dalam penerapanna, ppendekatan CTL mempunyai tujuh komponen utama, yaitu (1) konstrukttivisme (contructivisme), (2) menemukan (inquiry), (3) bertanya ( questioning), (4) masyarakat/ kelompok belajar (learning community), (5) pemodelan ( modeling), (6) refleksi ( reflection), dan (7) penilaian yang sebenarnya (authentic assesmen). Melalui pendekatan CTL tersebut, pengetahuan dan ketrampilan yang diperoleh siswa merupakan kontruksi dari pengalaman siswa yang bersangkutan.